Pengaruh NPM dan Current Ratio terhadap Financial Sustainability pada Perusahaan Farmasi yang Terdaftar di BEI Tahun 2014-2022 - Dwi Tiara, Wenti; Putra Prasetya, Bangun (PRIVE: Jurnal Riset Akuntansi dan Keuangan, 2024)
This study aims to determine the effect of Net Profit Margin (NPM) and Current Ratio on Financial Sustainability (FSR) in Pharmaceutical Sector Companies Listed on the IDX. The sample used in this research is 2 pharmaceutical sector companies listed on the Indonesia Stock Exchange for the period 2014 - 2022 and using purposive sampling method. The data analysis technique used is quantitative analysis. The data analysis method used is hypothesis testing including the F statistical test and the t statistical test. The results obtained in this study indicate that there is a significant effect of Net Profit Margin (NPM) and Current Ratio together on Financial Sustainability (FSR). Based on partial tests, there is a significant effect of Net Profit Margin (NPM) on Financial Sustainability (FSR). While Current Ratio has no significant effect on Financial Sustainability (FSR) in Pharmaceutical Sector Companies Listed on the IDX.